Work attitude, organizational commitment and emotional intelligence of Malaysian vocational college teachers - Ahad, Rosnee; Mustafa, Mohamad Zaid; Mohamad, Suhaimi; Abdullah, Nur Hanim Saadah; Nordin, Mohd Norazmi (Penerbit UTHM, 2021)
Emotional intelligence plays an important role in motivating a person to commit to a job. A person’s attitude while carrying out work makes emotional intelligence directed towards good productivity in the organization. This situation is also a major issue among vocational college teachers in Malaysia. There are issues where these teachers are unable to give a firm commitment to their organization due to their work attitude and emotional intelligence. This quantitative study was conducted to explore the relationship between work attitudes, organizational commitment and emotional intelligence among vocational college teachers in Malaysia. This study involved 263 respondents consisting of vocational college teachers throughout Malaysia. Analysis with Structural Equation Modelling (SEM) approach using Analysis of Moment Structures (AMOS) software was conducted. The results of the analysis show that, there is a significant positive relationship between work attitudes, organizational commitment and emotional intelligence. Therefore, this study can be used as a guide to stakeholders in managing vocational colleges, teachers and organizations properly.